TINJAUAN HUKUM PIDANA TERHADAP PELAKSANAAN UU NO. 23 TAHUN 1997 TENTANG PENGELOLAAN LINGKUNGAN HIDUP - Brahmanda, I Komang Agung Sri; Trinaya Dewi, A.A. Mas Adi (Kerta Dyatmika, 2024)
Criminal law serves as a coercive instrument to protect society from harmful acts, including those that result in environmental pollution. Environmental pollution refers to the entry of living organisms, substances, energy, and/or other components into the environment due to human activities, thereby reducing its quality to a level that renders it unfit for its intended function. This study aims to examine and understand the criminal law policy in the implementation of Law Number 23 of 1997 concerning Environmental Management, both in the present and in the future. The research employs a normative legal method with a statutory approach. The findings indicate that the current environmental criminal law policy has not been effectively enforced, as enforcement efforts are still limited to administrative warnings, with no criminal sanctions applied. Court decisions have not yet resulted in imprisonment or penal measures against perpetrators of environmental pollution. In the future, criminal law policy should be strengthened through enhanced environmental monitoring, particularly in relation to category C mineral mining activities that cause environmental degradation, and by developing environmental supervision manuals. The study concludes that the current enforcement of environmental criminal law policy remains suboptimal due to the absence of penal verdicts and insufficient governmental commitment to environmental protection. Future policy must include more rigorous oversight and the implementation of clear enforcement guidelines to ensure environmental sustainability.